Significant moments associated with psychic change - Mantilla Lagos, Carla (2021)
This research had the following objectives: 1) to identify, thematize and describe the significant moments of a psychoanalytic process perceived by the patients as important for the psychic change, as well as to analyze their nature and the relations between them, and the different aspects of the psychoanalytic process; 2) to evaluate if the perspective of the users on the significant moments of the psychotherapeutic process associated to the change contributes to extend the understanding of the therapeutic action of the psychoanalytic psychotherapy. The project has a qualitative approach, since a subjective phenomenon was taken as information (Mortl & Gelo, 2015), such as the user’s perception and assessment of aspects related to the psychoanalytic process that are related to psychic change, and the narrative of the lived process. The results show 4 thematic axes with 18 sub-themes in total that describe the moments perceived as important for the psychic change by the users.